Using the SGI Pro64 Open Source Compiler Infra-Structure for Teaching and Research - Amaral, José Nelson; Barton, Christopher; Macdonell, Andrew C.; McNaughton, Matthew (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
Modem optimizing compilers are complex programs that require from tens to hundreds of people-years to be developed. Thus professors must use third-party compiler infra-structures to introduce students to compiler optimizations. Until recently only infra-structures developed at universities, research institutes, or by GNU were widely available for teaching. However, in May 2000, SGI made public the source code for Pro64, a highly optimized suite of compilers for the Intel Architecture 64 (IA-64) that is an evolution of the established MIPSPro suite of compilers. The use of a production-level compiler infra-structure for teaching is thus new. In this paper we report our experience using the Pro64 in a graduate compiler optimization class. We paired the study of the Pro64 with the use of IMPACT within Trimaran, and with performance studies conducted with the MIPSPro compilers. The students feedback indicate that they valued working with a state-of-the-art compiler infrastructure and studying open research topics for their class projects.